2020
DOI: 10.3389/fgene.2020.00884
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Autosomal Short Tandem Repeats and Their Potential Association With Phenotype

Abstract: Forensic DNA profiling utilizes autosomal short tandem repeat (STR) markers to establish identity of missing persons, confirm familial relations, and link persons of interest to crime scenes. It is a widely accepted notion that genetic markers used in forensic applications are not predictive of phenotype. At present, there has been no demonstration of forensic STR variants directly causing or predicting disease. Such a demonstration would have many legal and ethical implications. For example, is there a duty t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 79 publications
0
38
0
2
Order By: Relevance
“…importance in terms of genetic markers (forensic applications) and perhaps even their functional role in regulation [33]. Despite this interest, little is known about the correction of their sequencing.…”
Section: Plos Onementioning
confidence: 99%
“…importance in terms of genetic markers (forensic applications) and perhaps even their functional role in regulation [33]. Despite this interest, little is known about the correction of their sequencing.…”
Section: Plos Onementioning
confidence: 99%
“…The amelogenin locus can also reveal persons inflicted with amelogenesis imperfecta, a disorder that affects the enamel on teeth. Variants at vWA and TPOX are associated with venous thromboembolism (Meraz‐Ríos et al, 2014), D8S1179, D5S818, and D2S1338 with gastric cancer, and TH01, D18S51, and D2S1338 with psychiatric disorders (Wyner et al, 2020). Any of the genomic markers that are used for forensic identification (i.e., STRs, SNPs, interspersed repeat sequences) can reveal persons who have mosaicisms, either natural or artificial.…”
Section: “Omics” and Privacy—past Present And Futurementioning
confidence: 99%
“…Genetic polymorphism analysis of STR loci has been utilized worldwide in many fields, including paternity detection, genetic mapping, disease linkage investigation, evolutionary biology, and the genetics of population. Our previous data showed that two autosomal STRs (TH01 and TPOX) were related to impulsive aggression, and the two other autosomal STRs (Penta D and Penta E) were involved in initiative aggression (Wyner et al., 2020 ; C. Yang et al., 2018 ). However, so far there have been no data to suggest the correlation between STRs on the autosomal chromosomes and male schizophrenia.…”
Section: Introductionmentioning
confidence: 99%